Engaging participants with research findings: A rights‐informed approach - Mathew Sunil George; Rakhal Gaitonde; Rachel Davey; Itismita Mohanty; Penney Upton (Wiley, 2023)
Abstract Background Sharing research findings with participants is recognized as an ethical imperative for the research community. However, most discourse on this topic in mainstream public health takes a paternalistic approach, with researchers retaining the power to choose if, when, and how research findings are shared. Methods Fieldwork took place from August 2018 to January 2019 and again from August 2019 to December 2019 among two communities in the south Indian state of Kerala. We integrated participant engagement with study findings into the research protocol, using various collaborative strategies identified during the design stage, forming partnerships with participants and determining appropriate forms of dissemination for different participant groups during fieldwork. Results Findings from previous research projects undertaken with these communities by other researchers had not been shared with them. This was interpreted by the communities as researchers not being interested in making a difference to their situation. In the current study, building reciprocal relationships that minimized power disparities, and providing outputs in tailored formats that promoted active engagement were key factors that enabled participants to engage with results. This engagement added value by enabling us to co‐develop study recommendations. This process also enabled the community to have ownership of the results and use them to advocate for health system change to improve access to health care. Conclusion Research should be transformative for participating communities. Participants have a right to know the results of the research they participate in since their knowledge provides the research data which can in turn promote community change. Operationalising this requires researchers to build partnerships with participants and their communities from the outset. The role of participants must be reimagined, and adequate resources should be built into the research process. This is both socially responsible and ethical, but also improves the impact and legitimacy of research for the participants and the communities that they represent. Patient or Public Contribution Participants of our research contributed to the design of various aspects of the engagement processes including the venue, the formats used for engagement, interpretation of the findings and recommendations from our research.